Immunotherapy combined with chemotherapy: a promising therapeutic approach in the management of colonic squamous cell carcinoma—a case report - Ren, Bingbing; Yang, Haitao; Mao, Yingying (Frontiers in Oncology, 2025)
Colorectal squamous cell carcinoma (CSCC) is an exceedingly rare malignancy, accounting for approximately 0.41% of all colorectal cancers. This case report describes a 52-year-old male with a history of chronic bronchitis, varicose vein of the lower limb, diabetes, and Hepatitis B cirrhosis, who presented with worsening abdominal pain. The patient underwent a right hemicolectomy, and postoperative pathology revealed a moderately differentiated CSCC with proficient mismatch repair (pMMR) status. The patient was initially treated with the CAPEOX adjuvant chemotherapy regimen, the patient’s condition unfortunately progressed. Therefore, the treatment plan has been adjusted to include nab-paclitaxel and carboplatin, in combination with camrelizumab, an Anti-PD-1 therapy, for antitumor therapy. The combination therapy resulted in a partial response. This case highlights the potential efficacy of Anti-PD-1 therapy combined with chemotherapy in CSCC, suggesting a possible treatment approach for this rare cancer subtype.